Influence of HIV infection on cognition and overall intelligence in HIV-infected individuals: advances and perspectives - Zaongo, Silvere D.; Harypursat, Vijay; Rashid, Farooq; Dahourou, Désiré Lucien; Ouedraogo, Abdoul-Salam; Chen, Yaokai (Frontiers in Behavioral Neuroscience, 2023)
It is now well understood that HIV-positive individuals, even those under effective ART, tend to develop a spectrum of cognitive, motor, and/or mood conditions which are contemporarily referred to as HIV-associated neurocognitive disorder (HAND), and which is directly related to HIV-1 infection and HIV-1 replication in the central nervous system (CNS). As HAND is known to induce difficulties associated with attention, concentration, and memory, it is thus legitimate and pertinent to speculate upon the possibility that HIV infection may well influence human cognition and intelligence. We therefore propose herein to review the concept of intelligence, the concept of cells of intelligence, the influence of HIV on these particular cells, and the evidence pointing to differences in observed intelligence quotient (IQ) scores between HIV-positive and HIV-negative individuals.Additionally, cumulative research evidence continues to draw attention to the influence of the gut on human intelligence. Up to now, although it is known that HIV infection profoundly alters both the composition and diversity of the gut microbiota and the structural integrity of the gut, the influence of the gut on intelligence in the context of HIV infection remains poorly described. As such, we also provide herein a review of the different ways in which HIV may influence human intelligence via the gut-brain axis. Finally, we provide a discourse on perspectives related to HIV and human intelligence which may assist in generating more robust evidence with respect to this issue in future studies. Our aim is to provide insightful knowledge for the identification of novel areas of investigation, in order to reveal and explain some of the enigmas related to HIV infection.